Sistema especialista para aplicação de coagulante no tratamento de água : implementação em tempo real - Zaque, Ricardo Augusto Moraes (2018)
In most Brazilian municipalities, the water supply service comes from surface water sources, which, of course, implies demands for infrastructure and human resources, especially for the treatment of water. In a context of significant deficiencies (infrastructure and human resources) ancillary methodologies and/or substitutes are of great value. This work aimed to develop an Expert System (ES) to determine and apply the coagulant dose, in real time, in a Water Treatment Plant (WTP). For this, the ES was developed, implemented and evaluated in a case study, which was chosen the WTP of the city of Nobres, in the State of Mato Grosso. As a result, an ES, called IAD-SA (Artificial Intelligence for Dosage of Aluminum Sulphate), was obtained (certified by the Turing test), capable of determining and applying the dose of coagulant in the treatment of water. As a conclusion, IAD-SA was able to contribute to the operation of WTP-Nobres and could contribute with other WTPs, making a decision and applying the dose of coagulant necessary for the treatment of water